Membrane nanotubes between peritoneal mesothelial cells: functional connectivity and crucial participation during inflammatory reactions - Ranzinger, Julia; Rustom, Amin; Schwenger, Vedat (Frontiers in Physiology, 2014)
Peritoneal dialysis (PD) has attained increased relevance as continuous renal replacement therapy over the past years. During this treatment, the peritoneum functions as dialysis membrane to eliminate diffusible waste products from the blood-stream. Success and efficacy of this treatment is dependent on the integrity of the peritoneal membrane. Chronic inflammatory conditions within the peritoneal cavity coincide with elevated levels of proinflammatory cytokines leading to the impairment of tissue integrity. High glucose concentrations and glucose metabolites in PD solutions contribute to structural and functional reorganization processes of the peritoneal membrane during long-term PD. The subsequent loss of ultrafiltration is causal for the treatment failure over time. It was shown that peritoneal mesothelial cells are functionally connected via Nanotubes (NTs) and that a correlation of NT-occurrence and defined pathophysiological conditions exists. Additionally, an important participation of NTs during inflammatory reactions was shown. Here, we will summarize recent developments of NT-related research and provide new insights into NT-mediated cellular interactions under physiological as well as pathophysiological conditions.